Ileocecal lipomatosis presenting as intermittent intestinal obstruction and hematochezia: case report with literature review - Keerthi, Nemalidinne; K., Mohan Kumar; Baig, Asadullah; Vogu, Sudeep; P. N., Sreeramulu (International Surgery Journal, 2018)
Lipomatosis of the ileocecal valve is defined as the submucosal infiltration or accumulation of adipose tissue in the ileocecal region, usually resulting in non-specific gastrointestinal symptoms like abdominal distension, abdominal discomfort, vomiting, alternating diarrhea and constipation and occasionally bleeding per rectum. Lipomas are the most common benign mesenchymal tumors of the gastrointestinal tract. Distribution of alimentary lipomas demonstrates a predilection for the colon, but they may originate anywhere in the gastrointestinal tract. Here, we are describing the case of an elderly male who presented with rectal bleeding. Both colonoscopy and computed tomography of the abdomen and pelvis confirmed the presence of a mass near the ileocecal valve. Because of bleeding, the patient required right hemicolectomy to resect the lesion. Both macroscopic and microscopic pathology were consistent with lipoma at the ileocecal valve. Previous cases of ileocecal valve lipomas have been reported in the literature, with the majority presenting as intussusception or volvulus. We present a rare case of an ileocecal valve lipoma with superficial ulceration presenting as lower gastrointestinal bleeding that was treated successfully with resection.